2022
DOI: 10.3389/fcell.2022.948812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decellularized extracellular matrix derived from Jagged1-treated human dental pulp stem cells on biological responses of stem cells isolated from apical papilla

Abstract: Objective: Indirect Jagged1 immobilization efficiently activates canonical Notch signaling in human dental pulp stem cells (hDPSCs). This study aimed to investigate the characteristics of the Jagged1-treated hDPSC-derived decellularized extracellular matrix (dECM) and its biological activity on odonto/osteogenic differentiation of stem cells isolated from apical papilla (SCAPs).Methods: Bioinformatic database of Jagged1-treated hDPSCs was analyzed using NetworkAnalyst. hDPSCs seeded on the Jagged1 immobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Decellularized ECM basically preserves the microenvironment and fibrin, mimics natural tissues chemically and mechanically, provides mechanical support for cell seeding and biological 3D carriers, and is considered a suitable natural scaffold material for endodontic tissue engineering [32] . Dental pulpderived decellularized ECM, which produces scaffolds that support the proliferation, differentiation, and regulation of mineralization [33,34] of stem cells, has no apparent cytotoxicity. Animal experiments demonstrated that decellularized ECM containing bone morphogenetic protein 4 (BMP-4) bound to DPSCs, and vascularized pulp histogenesis was observed in nude mice [35] .…”
Section: Acellular Ecmmentioning
confidence: 99%
“…Decellularized ECM basically preserves the microenvironment and fibrin, mimics natural tissues chemically and mechanically, provides mechanical support for cell seeding and biological 3D carriers, and is considered a suitable natural scaffold material for endodontic tissue engineering [32] . Dental pulpderived decellularized ECM, which produces scaffolds that support the proliferation, differentiation, and regulation of mineralization [33,34] of stem cells, has no apparent cytotoxicity. Animal experiments demonstrated that decellularized ECM containing bone morphogenetic protein 4 (BMP-4) bound to DPSCs, and vascularized pulp histogenesis was observed in nude mice [35] .…”
Section: Acellular Ecmmentioning
confidence: 99%
“…Recent studies have illustrated the regenerative potential of decellularized extracellular matrix (dECM) obtained from DPSCs for bone tissue regeneration, as it promotes mineralization (8). In addition, dECM generated from immobilized Jagged1-treated hDPSCs increases the odonto/osteogenic differentiation of stem cells isolated from the apical papilla (SCAPs) (9).…”
Section: Introductionmentioning
confidence: 99%